A cell cycle role for the epigenetic factor CTCF-L/BORIS. - Manuel Rosa-Garrido (Public Library of Science (PLoS), 2012)
CTCF is a ubiquitous epigenetic regulator that has been proposed as a master keeper of chromatin organisation. CTCF-like, or BORIS, is thought to antagonise CTCF and has been found in normal testis, ovary and a large variety of tumour cells. The cellular function of BORIS remains intriguing although it might be involved in developmental reprogramming of gene expression patterns. We here unravel the expression of CTCF and BORIS proteins throughout human epidermis. While CTCF is widely distributed within the nucleus, BORIS is confined to the nucleolus and other euchromatin domains. Nascent RNA experiments in primary keratinocytes revealed that endogenous BORIS is present in active transcription sites. Interestingly, BORIS also localises to interphase centrosomes suggesting a role in the cell cycle. Blocking the cell cycle at S phase or mitosis, or causing DNA damage, produced a striking accumulation of BORIS. Consistently, ectopic expression of wild type or GFP- BORIS provoked a higher rate of S phase cells as well as genomic instability by mitosis failure. Furthermore, down-regulation of endogenous BORIS by specific shRNAs inhibited both RNA transcription and cell cycle progression. The results altogether suggest a role for BORIS in coordinating S phase events with mitosis.